Characterization of the 11-year solar signal using a multiple regression analysis of the ERA-40 dataset - Crooks, SA; Gray, L (2005)
A multiple linear regression analysis of the ERA-40 dataset for the period 1979-2001 has been used to study the influence of the 11-yr solar cycle on atmospheric temperature and zonal winds. Volcanic, North Atlantic Oscillation (NAO), ENSO, and quasi-biennial oscillation (QBO) signatures are also presented. The solar signal is shown to be readily distinguishable from the volcanic signal. The main solar signal is a statistically significant positive response (i.e., warmer in solar maximum) of 1.75 K over the equator with peak values at 43 km and a reversed signal of similar magnitude at high latitudes that is seasonally dependent. Consistent with this is a statistically significant zonal wind response of up to 6 m s -1 in the subtropical upper stratosphere/lower mesosphere that is also seasonally dependent. The wind anomalies are westerly/easterly in solar maximum /minimum. In addition, there is a statistically significant temperature response in the subtropical lower stratosphere that shows similarity in spatial structure to the QBO response, suggesting a possible interaction between the solar and QBO signals in this region. The solar response in tropospheric zonal winds is small but significant, confirming previous studies that indicate a possible modulation of the Hadley circulation. © 2005 American Meteorological Society.